Accurate leakage current models for MOSFET nanoscale devices - Abdoul Rjoub; Mamoun Mistarihi; Nedal Al Taradeh (Institute of Advanced Engineering and Science, 2020)
This paper underlines a closed forms of MOSFET transistor’sleakage current mechanisms inthe sub 100nmparadigm.The incorporation of draininduced barrier lowering (DIBL), Gate Induced Drain Lowering (GIDL) and body effect (m) on the sub-threshold leakage (Isub) wasinvestigated in detail. The Band-To-Band Tunneling (IBTBT) due to the source and Drain PN reverse junction were also modeled witha close and accurate model using a rectangularapproximation method (RJA). The three types of gate leakage (IG) were also modeled and analyzed for parasitic (IGO), inversion channel (IGC), and gate substrate (IGB).In addition, the leakage resources due to the aggressive reduction in the oxide thickness (